Proyecto para la implementación de una radio comunitaria en la parroquia de Guayllabamba - Álvarez Puma, Doris Viviana (2013)
The present work is to show that radio is the most appropriate means of communication due to its coverage. The medium since its inception has been evolving in all fields, especially technical and proposed formats that are used in transmissions. Since the birth of the stations so far we can identify two types of stations: the operation dependent commercial enterprises or commercial forms that guide their spaces. And community radio, the same who had their heyday in Latin America for several decades and laid the groundwork for today's youth and adults showing revive interest in several areas of the country. This station is non-poor programming, contrary are its inhabitants who appropriate radio and makes them function in each zone grill.